2016
DOI: 10.1111/cdev.12671
|View full text |Cite
|
Sign up to set email alerts
|

What Paves the Way to Conventional Language? The Predictive Value of Babble, Pointing, and Socioeconomic Status

Abstract: A child's first words mark the emergence of a uniquely human ability. Theories of the developmental steps that pave the way for word production have proposed that either vocal or gestural precursors are key. These accounts were tested by assessing the developmental synchrony in the onset of babbling, pointing, and word production for 46 infants observed monthly between the ages of 9 and 18 months. Babbling and pointing did not develop in tight synchrony and babble onset alone predicted first words. Pointing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 78 publications
5
95
1
3
Order By: Relevance
“…Moreover, demonstrating that an infant or child can learn from overheard speech does not make this an efficient or advantageous path to language learning. Indeed, language input that meaningfully builds on what children are doing in the moment, is rooted in shared attention, and models the use of syntax by using recasts and expansions of their utterances best facilitates language learning (e.g., Harris, Golinkoff, & Hirsh-Pasek, 2010;Malin, Cabrera, & Rowe, 2014;McGillion et al, 2017). As countless studies have shown, back-and-forth conversations that are both temporally and topically contingent on children's contribution, are the fuel that prime the learning of language (Goldin-Meadow et al, 2014;Reed, Hirsh-Pasek, & Golinkoff, 2017;Romeo et al, 2018;Tamis-LeMonda, Kuchirko, & Song, 2014).…”
Section: Speech Directed To Children Supports Language Learningmentioning
confidence: 99%
“…Moreover, demonstrating that an infant or child can learn from overheard speech does not make this an efficient or advantageous path to language learning. Indeed, language input that meaningfully builds on what children are doing in the moment, is rooted in shared attention, and models the use of syntax by using recasts and expansions of their utterances best facilitates language learning (e.g., Harris, Golinkoff, & Hirsh-Pasek, 2010;Malin, Cabrera, & Rowe, 2014;McGillion et al, 2017). As countless studies have shown, back-and-forth conversations that are both temporally and topically contingent on children's contribution, are the fuel that prime the learning of language (Goldin-Meadow et al, 2014;Reed, Hirsh-Pasek, & Golinkoff, 2017;Romeo et al, 2018;Tamis-LeMonda, Kuchirko, & Song, 2014).…”
Section: Speech Directed To Children Supports Language Learningmentioning
confidence: 99%
“…Infant's prelinguistic vocalizations and gestures predict later language abilities (Bates, Benigni, Bretherton, Camaioni, & Volterra, ; Igualada, Bosch, & Prieto, ; Laakso, Poikkeus, Katajamaki, & Lyytinen, ; McCune & Vihman, ; McGillion, Herbert, et al, ). The question addressed in this study is whether this is because they represent instances of prelinguistic intentional communication.…”
Section: Studymentioning
confidence: 99%
“…Infants learn that vocalizing at different times during quasiperiodic cycles of mandibular opening and closure results in vowels, at maximal mandibular opening, and consonants, at maximal mandibular closure. However, it is still unclear how these early syllable rhythms in babbling contribute to later adult rhythms or later language capacities in general . Results from nonhuman animals suggest that animal babbling is not linked in a simple way to later adult vocal production.…”
Section: Human and Nonhuman Studies Of Vocal Rhythmmentioning
confidence: 99%
“…However, it is still unclear how these early syllable rhythms in babbling contribute to later adult rhythms or later language capacities in general. 55 Results from nonhuman animals suggest that animal babbling is not linked in a simple way to later adult vocal production. For example, female sac-winged baby bats, during the babbling period, produce adult male songs and trills without producing them as adults.…”
Section: Babbling and Stutteringmentioning
confidence: 99%